Proposals for Second Five Year Plan as Presented to the Planning Commission Government of Rajasthan - Planning Commission (Planning Commission, 1955)
The collective and classical denomination represented by the name Rajasthan today came into being late in 1949 as a result of the integration of 22 princely States and Chiefships. Frequent occurrences of famine or scarcity conditions resulted in even greater backwardness of the States. Banning a few exceptions, no administrative system could be built up and the people remained under the autocratic rule of the princes.
Government of Rajasthan Planning Department